Inducible Nitric Oxide Is Essential for Host Control of Persistent but Not Acute Infection with the Intracellular Pathogen Toxoplasma gondii - Scharton-Kersten, Tanya M. (The Rockefeller University Press, 1997)

(untitled)
The induction by IFN-γ of reactive nitrogen intermediates has been postulated as a major mechanism of host resistance to intracellular pathogens. To formally test this hypothesis in vivo, the course of Toxoplasma gondii infection was assessed in nitric oxide synthase (iNOS)−/− mice. As expected, macrophages from these animals displayed defective microbicidal activity against the parasite in vitro. Nevertheless, in contrast to IFN-γ−/− or IL-12 p40−/− animals, iNOSdeficient mice survived acute infection and controlled parasite growth at the site of inoculation. This early resistance was ablated by neutralization of IFN-γ or IL-12 in vivo and markedly diminished by depletion of neutrophils, demonstrating the existence of previously unappreciated NO independent mechanisms operating against the parasite during early infection. By 3-4 wk post infection, however, iNOS knockout mice did succumb to T. gondii. At that stage parasite expansion and pathology were evident in the central nervous system but not the periphery suggesting that the protective role of nitric oxide against this intracellular infection is tissue specific rather than systemic.